TRIAL OF SCAR IN PATIENTS WITH PREVIOUS ONE CAESAREAN SECTION - Sadaf, Rabeea; Nasreen, Abida; Zahid, Muhammad (Journal of Postgraduate Medical Institute, 2011)
Objective: To assess the usefulness of trial of scar in patients with previous one cesarean section and to know the frequency of vaginal delivery and repeat caesarean section (CS) in these patients. Material and Methods: This descriptive study was conducted from July 2001 to June 2002, at Khyber Teaching Hospital Peshawar on 50 pregnant women with a history of previous one cesarean section and with no contraindication for vaginal delivery. Patients with more than one CS and those with medical disorders were excluded. A detailed history and examination of each patient was done. The clinical data was recorded in proformas and the results were tabulated. Results: Among 50 pregnant women with previous one CS, 36 (72%) patients were successfully delivered vaginally while 14(28%) had emergency lower segment CS. Out of 36 vaginal deliveries, 27 (75%) were normal vaginal deliveries while 9 (25%) were delivered with instrumental support i.e. 7 (19.4%) with outlet forceps and 2 (5.6%) by vacuum extraction. One patient (2%) developed scar dehiscence and lost her baby which resulted in one still birth (2%) in this study. One (2%) patient with imminent rupture underwent timely CS and baby was saved. Conclusion: A trial of scar may be given to all pregnant women with previous cesarean section except those with absolute contraindications. A woman with one previous cesarean section delivery with a low transverse incision should be counseled and encouraged to attempt labor in her current pregnancy.